Faktor-faktor Pertimbangan Mahasiswa UNILA dalam Pemilihan Rumah Indekos dikelurahan Kampung Baru dan Gedung Meneng Bandar Lampung - Setyo Wijoyo; Emi Maimunah (Jurnal Ekonomi Pembangunan, 2019)
This study aims to determine what factors are considered by Lampung University students by choosing boarding houses. The data used are primary data obtained from the questionnaires' results, which are data on students' perceptions by choosing boarding homes. The sampling technique used was the Non-Probability Sampling method with the type of Convenience Sampling. This research uses a descriptive quantitative method. This study concludes that factors are considered students to a selection of boarding houses in Kampung Baru and GedungMeneng Bandar Lampung: variable with average, reference, rental price, location excellence, and facilities completeness.